Head Anthropometric of Malaysian Male Adults Using 3D Scanning - Syahrizan Azlan; Mustafa El Bakri, Helmy; Mahmood, Salwa; Muhamad Dzahir, Nur Fitrah Najiha (Journal of Advanced Industrial Technology and Application, 2024)
Safety helmets are essential for protecting individuals in high-risk industries such as construction, sports, and manufacturing, where head injuries are common. Despite their importance, poor helmet fit is widespread, primarily due to a lack of consideration for anthropometric diversity, which reduces their effectiveness and compromises safety. Anthropometry, the study of human body measurements, played a critical role in this research. Current helmet designs are predominantly based on Western anthropometric data, which fail to accommodate the unique head shapes of Malaysians. To bridge this gap, the study involved 3D scans of 100 Malaysian male participants at UTHM, capturing key anthropometric dimensions such as head circumference, width, and length. These measurements were taken with and without helmets to thoroughly analyze fit discrepancies. The findings highlighted significant anthropometric variations within the population, revealing that many existing helmets did not provide a proper fit. This study emphasizes the importance of incorporating localized anthropometric data in helmet design, offering a solution that improves comfort, enhances safety, and reduces the likelihood of head injuries.